Clinical Outcome Data of First Cohort of Chronic Pain Patients Treated With Cannabis‐Based Sublingual Oils in the United Kingdom: Analysis From the UK Medical Cannabis Registry. (5th October 2021) - Kawka, Michal; Erridge, Simon; Holvey, Carl; Coomber, Ross; Usmani, Azfer; Sajad, Mohammad; Platt, Michael W.; Rucker, James J.; Sodergren, Mikael H.
Abstract: Cannabis‐based medicinal products (CBMPs) are an emerging therapeutic option in the management of primary chronic pain, using the role of the endocannabinoid system in modulating central and peripheral pain processes. Despite promising preclinical data, there is a paucity of high‐quality evidence to support the use of CBMPs for chronic pain. This study aimed to investigate the health‐related quality‐of‐life outcomes of patients with chronic pain who were prescribed CBMP oil preparations (Adven, Curaleaf International, Guernsey, UK). This study is a case series of patients from the UK Medical Cannabis Registry, who were treated with CBMP oils for an indication of chronic pain. The primary outcomes were the changes in Brief Pain Inventory short form, Short‐Form McGill Pain Questionnaire‐2, Visual Analog Scale Pain, General Anxiety Disorder‐7, Sleep Quality Scale, and EQ‐5D‐5L, at 1, 3, and 6 months. One hundred ten patients were included. Significant improvements in Sleep Quality Scale, EQ‐5D‐5L pain and discomfort subscale, and Brief Pain Inventory Interference Subscale ( P < .05) at 1, 3, and 6 months were demonstrated. There were no notable differences between cannabis‐naïve and previous cannabis users in quality‐of‐life outcomes. The adverse event incidence was 30.0%, with most (n = 58; 92.1%) adverse events being mild or moderate in intensity. Treatment of chronic pain with Adven CBMP oils was associated with an improvement in pain‐specific outcomes, health‐related quality of life, and self‐reported sleep quality. Relative safety was demonstrated over medium‐term prescribed use. While these findings must be treated with caution considering the limitations of study design, they can inform future clinical trials.